Application of bibliographic managers for the production of academic texts in students of an institute - Romani Pillpe, Guillermo (2022)
The objective of this work was to determine the effect of the application of bibliographic managers as a strategy for the production of academic texts in students of the Instituto de Educación Superior Tecnológico Público Federico Uranga, Pisco. For this, the following methodology was obtained; the type applied, explanatory level, pre-experimental design and quantitative approach. We worked with 38 students from the first semester 2021 -1 in the Production and Interpretation of Texts course in the Food Industries Study Program. For the contracting of hypotheses, the Wilcoxon signed rank test was obtained. The results indicated that when comparing the mean range pre-test 35.92 and post-test 85.74 that there is a statistically significant difference. It was concluded that the use of bibliographic managers significantly influences the production of academic texts.